MTHFD1 controls DNA methylation in Arabidopsis - Groth, Martin; Wirtz, Markus; Hell, Rüdiger (Nature Communications, 2016)
DNA methylation contributes to transcriptional silencing. Here, Groth et al.show that mutant plants defective in MTHFD1, an enzyme involved in folate metabolism, have a DNA hypomethylation phenotype highlighting the link between one-carbon metabolism and DNA methylation, which is mediated by SAM as a common methyl donor.
Gesehen am 29.05.2017